THE PHENOMENA OF DIENG PLATEAU TOURISMDESTINATION DEVELOPMENT PLANNING - Hariwanto, Army Tunggu (Journal of Indonesian Tourism and Policy Studies, 2021)
The tourism sector can be one of the mainstay sectors in the economic growth of the Dieng Plateau. One of the tourism problems in the Dieng Plateau is about accessibility and supporting infrastructure. Even though the existing road infrastructure is quite good, it can be improved again by widening the road access so that even large vehicles can easily cross it and needs to be improved also for other infrastructure such as hotels, restaurants, promotions, and others. The number of folklore or history in the Dieng area is the main factor to attract tourists and is also supported by beautiful natural scenery. To visit this destination, tourists need about 9 - 10 hours from Jakarta / Bogor. Access from the Jati Asih Toll Road, Bekasi to the Weleri Toll Exit Gate can be reached using the Trans Java Toll Road. To go through the Trans Java Toll, drivers have to pay toll fees which are quite expensive. And road users are also required to always prepare enough fuel because the distance between the Rest Areas is quite far. It should also be remembered that motorists who pass this route must remain vigilant and careful and pay attention to the condition of their vehicles because the bumpy road and the many potholes on the Trans Java Toll Road are very prone to traffic accidents. This study aims to analyze the planning for the development of tourism destinations in the Dieng Plateau